An effective dialysis method for surface funtionalization of nanoparticles in liquid phase - Sample: Porphyrine derivatives @ ZnO-Nanorods - Klaumünzer, Martin; Münzel, C.; Burger, Alexandra; Mackovic, Mirza; Voigt, Michael; Spiecker, Erdmann; Hirsch, Andreas; Peukert, Wolfgang (Nanotechnology 2013: Advanced Materials, CNTs, Particles, Films and Composites - 2013 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2013, 2013)
In order to optimize electron transfer and optoelectronic properties in nanoparticulate thin films for electronics we show the surface functionalization of ZnO nanorods by exchanging the stabilizing 2-[2-(2-Mefhoxyefhoxy)-ethoxy] acetic acid at the ZnO surface with redoxactive organic molecules. Surface functionalization is undertaken by an efficient dialysis method. Emission- and absorption-spectroscopy indicate an effective electronic interaction between the ZnO nanorods and the pophyrine derivatives. In addition, we discuss on the binding mechanism and the ligand exchange kinetics of the porphyrine molecules. Our experiments suggest a better and faster binding to the ZnO nanorod surface for porphyrine A than for porphyrine B. This can be explained by steric effects. Moreover we claim a fourfold anchored binding for porphyrine A and we shed light on entropic effects during ligand exchange.

Application of Printable ITO/PEDOT Nanocomposites as Transparent Electrodes in Optoelectronic Devices - Maksimenko, Ilja; Kilian, Daniel; Mehringer, Christian; Voigt, Michael; Peukert, Wolfgang; Wellmann, Peter (Conference on Lasers and Electro-Optics, 2012)
Printable transparent hybrid composites consisting of indium tin oxide (ITO) nanoparticles and conducting polymer 3,4-polyethylenedioxythiophene: polystyrene sulfonic acid (PEDOT:PSS)) as matrix material were developed and used as transparent electrodes in all-printed flexible electroluminescent lamps and electrochromic display
Keywords: optical devices; electro-optical devices; thin films; transparent conductive coatings

Detailed Analysis of the Growth Kinetics of ZnO Nanorods in Methanol - Voigt, Michael; Klaumünzer, Martin; Thiem, Heiko; Peukert, Wolfgang (Journal of Physical Chemistry C, 2010)
The growth kinetics of ZnO nanorods in methanol is studied by a combination of scanning and high-resolution transmission electron microscopy and X-ray diffraction analysis. In the early stage of growth oriented attachment of 2−3 spheroidal crystallites to rod-like structures occurs. Later, rods of up to 90 nm in length with a hexagonal cross-section up to 18 nm in diameter form by ripening. Our main finding is that the growth follows a power law as a function of the ripening time with exponents of 0.32 to 0.39 for the length and 0.17 to 0.21 for the diameter. In contrast to previous studies on the growth of ZnO rods in alcohols our results indicate that the growth is dominated by anisotropic Ostwald ripening that is limited by volume diffusion.

Evaluation of the film formation and the charge transport mechanism of indium tin oxide nanoparticle films - Mahajeri, Mahdi; Voigt, Michael; Klupp Taylor, Robin; Reindl, Armin; Peukert, Wolfgang (Thin Solid Films, 2010)
The structure formation and charge transfer of thin nanoparticulate indium tin oxide (ITO) films prepared by dip-coating was studied as a function of stabilizer before and after annealing at different temperatures. The analysis of the film structure by optical methods revealed that it is a function of the stability. Suspensions containing an optimum stabilizer concentration of 0.1 mol/l resulted in densely packed films with a peak specific conductivity of 8.3 S cm− 1 after annealing at 550 °C for 1 h in air and 121 S cm− 1 after annealing in forming gas at 250 °C for 1 h, respectively. Furthermore, for the densely packed films fluctuation-induced tunnelling was found to be the dominant charge transport mechanism, whereas for the low density films a thermally activated charge transport was observed. That the films of maximum density showed a metallic charge transport behaviour at temperatures above 300 K indicated the optimal contact between ITO particles had been achieve
Keywords: Indium tin oxide; Nanoparticles; Dispersion; Stability; Transmittance; Conductance; Charge transport

Fabrication, charge carrier transport, and application of printable nanocomposites based on indium tin oxide nanoparticles and conducting polymer 3,4-ethylenedioxythiophene/polystyrene sulfonic acid - Maksimenko, Ilja; Kilian, Daniel; Mehringer, Christian; Voigt, Michael; Peukert, Wolfgang; Wellmann, Peter (Journal of Applied Physics, 2011)
Printable transparent hybrid composites consisting of indium tin oxide (In2O3:Sn; ITO) nanoparticles and conducting polymer 3,4-polyethylenedioxythiophene (PEDOT) as matrix material were developed. The basic idea is to fill up the pores of the highly porous nanoparticulate ITO network to improve the interparticle contact and hence the conductivity of printed ITO thin films. Ready-to-use and stable aqueous dispersions were fabricated starting from ITO nanoparticles and aqueous formulation of conducting PEDOT and polystyrene sulfonic acid (PSS). This report presents and discusses key factors to obtain stable ITO-PEDOT dispersions with different mixing ratios and their application for printable devices as transparent electrode material. It was found that the f-potential value is crucial for preparation of stable dispersions. Electrical and optical properties of the hybrid ITO-PEDOT coatings were analyzed. Temperature dependent resistivity measurements reveal that conduction occurs by fluctuation induced tunneling. Transparent and conducting nanocomposite layers with a conductivity as high as 132 X1cm1 were fabricated by a low-temperature (T¼130 C) and entirely vacuum-free process. An all-printed electroluminescent lamp on a flexible substrate was realized as a demonstrator showing the applicability of such coatings for voltage-driven optoelectronic devices.<br

Gas phase temperature measurements in a flame spray pyrolysis process by O2 pure rotational CARS - Peukert, Wolfgang; Seeger, Thomas; Engel, Sascha; Kögler, Andreas; Gao, Yi; Kilian, Daniel; Voigt, Michael; Leipertz, Alfred (Laser Applications to Chemical, Security and Environmental Analysis 2012, 2012)
For the production of oxide nanoparticles at a commercial scale, flame spray processes are frequently used. To preserve the original behavior of the sensitive flame spray pyrolysis process in situ, the gas phase temperatures were measured with pure rotational CARS. An O pure rotational CARS setup was applied due to the lack of N. The CARS technique benefit from a polarization filtering technique that is essential in particle and droplet environments for acquiring CARS spectra suitable for temperature fitting. The temperature results indicate the dissipation of energy by radiation in the presence of particles since the flame temperatures are decreasing with increasing particle concentrations. © 2012 OS
Keywords: flame; spray; pyrolysis; gas; phase; particle; nano; radiation

Gas phase temperature measurements in the liquid and particle regime of a flame spray pyrolysis process using O2-based pure rotational coherent anti-Stokes Raman scattering - Peukert, Wolfgang; Engel, Sascha; Kögler, Andreas; Gao, Yi; Kilian, Daniel; Voigt, Michael; Seeger, Thomas; Leipertz, Alfred (Applied Optics, 2012)
For the production of oxide nanoparticles at a commercial scale, flame spray processes are frequently used where mostly oxygen is fed to the flame if high combustion temperatures and thus small primary particle sizes are desired. To improve the understanding of these complex processes in situ, noninvasive optical measurement techniques were applied to characterize the extremely turbulent and unsteady combustion field at those positions where the particles are formed from precursor containing organic solvent droplets. This particle-forming regime was identified by laser-induced breakdown detection. The gas phase temperatures in the surrounding of droplets and particles were measured with O2 -based pure rotational coherent anti-Stokes Raman scattering (CARS). Pure rotational CARS measurements benefit from a polarization filtering technique that is essential in particle and droplet environments for acquiring CARS spectra suitable for temperature fitting. Due to different signal disturbing processes only the minority of the collected signals could be used for temperature evaluation. The selection of these suitable signals is one of the major problems to be solved for a reliable evaluation process. Applying these filtering and signal selection steps temperature measurements have successfully been conducted. Time-resolved, single-pulse measurements exhibit temperatures between near-room and combustion temperatures due to the strongly fluctuating and flickering behavior of the particle-generating flame. The mean flame temperatures determined from the single-pulse data are decreasing with increasing particle concentrations. They indicate the dissipation of large amounts of energy from the surrounding gas phase in the presence of particles.
Keywords: oxyide; nanoparticle; optical; noninvasive; droplet; combustion; raman; scattering

Morphological impact of zinc oxide layers on the device performance in thin-film transistors - Faber, Hendrik; Klaumünzer, Martin; Voigt, Michael; Galli, Diana; Vieweg, Benito; Peukert, Wolfgang; Spiecker, Erdmann; Halik, Marcus (Nanoscale, 2011)
Zinc oxide thin-films are prepared either by spin coating of an ethanolic dispersion of nanoparticles (NP, diameter 5 nm) or by spray pyrolysis of a zinc acetate dihydrate precursor. High-resolution electron microscopy studies reveal a monolayer of particles for the low temperature spin coating approach and larger crystalline domains of more than 30 nm for the spray pyrolysis technique. Thin-film transistor devices (TFTs) based on spray pyrolysis films exhibit higher electron mobilities of up to 24 cm² V−1 s−1 compared to 0.6 cm² V−1 s−1 for NP based TFTs. These observations were dedicated to a reduced number of grain boundaries within the transistor channel.

Nanogap-controllable self-assembly of gold nanoparticles using nanotrench template - Sugano, Kouji; Hiraoka, Ryoji; Tsuchiya, Toshiyuki; Tabata, Osamu; Klaumünzer, Martin; Voigt, Michael; Peukert, Wolfgang (2011 16th International Solid-State Sensors, Actuators and Microsystems Conference, TRANSDUCERS'11, 2011)
This paper reports high-yield self-assembly process for gold nanoparticle with a diameter of 60 nm, which can precisely control an interparticle nanogap ranging from 0 to 60 nm, using a template-assisted self-assembly with a pair of circular nanotrenches. A center-to-center distance of nanotrenches was changed in order to control an interparticle nanopgap. We found that an assembly yield strongly depends on a particle-particle interaction and achieved nanogap-controlled particle arrangement with high yield by controlling the particle-particle interaction with an addition of an electrolyte. This technique would enable us to control plasmonic resonance property of a nanoparticles pair for many emerging applications. © 2011 IEE
Keywords: Nanoparticle; Nanogap; Self-Assembly; Plasmon

Optimum between purification and colloidal stability of ZnO nanoparticles - Marczak, Renata; Segets, Doris; Voigt, Michael; Peukert, Wolfgang (Advanced Powder Technology, 2010)
Crystalline ZnO quantum dots have been synthesized by hydrolysis of zinc acetate dihydrate with lithium hydroxide in ethanolic solution. By varying different parameters of the synthesis process, the size of the ZnO particles can be controlled. Detailed investigation of the ripening of the nanoparticles evidenced that despite of the well-known influence of ageing temperature and time, the presence of the reaction byproduct lithium acetate strongly affects the ripening behaviour. In particular, the particle size can be almost completely arrested by the removal of this byproduct via reversible flocculation of the ZnO nanoparticles using heptane as an antisolvent. A closer analysis of the repeated washing process shows an initial improvement of the colloidal stability of the ZnO nanoparticles during the first purification cycle as it mainly removes the lithium acetate from the suspension and not the stabilizing acetate groups directly bound to the particle surface. With further washing the remaining acetate ligands are unable to maintain the stabilization against agglomeration of the ZnO nanoparticles. Thus, there exists an optimum between purification progress and colloidal stability. These findings are also confirmed by calculations according to the DLVO theory, which show that there exists nearly no primary minimum of small ZnO nanoparticles below 5 nm in the presence of stabilizing acetate ions whereas the decrease in acetate ions bound to the particle surface leads to a more and more pronounced primary minimum. The present work is of particular significance for the preparation of purified colloidal ZnO nanoparticles for studies of their electrical and optical properties with respect to their wide range of potential applications.

Phase Transition Behavior and Oriented Aggregation During Precipitation of In(OH)3 and InOOH Nanocrystals - Klaumünzer, Martin; Mackovic, Mirza; Ferstl, Pascal; Voigt, Michael; Spiecker, Erdmann; Meyer, Bernd; Peukert, Wolfgang (Journal of Physical Chemistry C, 2012)
The phase transition behavior and oriented aggregation (OA) during colloidal synthesis of In(OH)3 nanocrystals in water are investigated by TEM, SEM, X-ray diffraction, and density functional theory (DFT) calculations. Besides the cubic In(OH)3 phase, also orthorhombic InOOH is formed in a precipitation route using indium acetate as the In3+ source. Well-developed nano- and microcuboids are observed that consist solely of In(OH)3. In contrast, the InOOH phase remains semicrystalline even for long reaction (refluxing) times. The irregular growth of the InOOH phase is explained by proton transfers from hydroxyl groups to oxygen ions within the InOOH lattice that lead to OH disorder and lattice strain. DFT calculations of the surface energies of ideal and water-saturated low-index InOOH and In(OH)3 surfaces predict that the In(OH)3 phase becomes energetically more favorable than InOOH above a critical crystallite size. This explains why InOOH is formed before the In(OH)3 phase, which is an unusual pathway for a hydrothermal process. Once InOOH has transformed to In(OH)3 by incorporation of water, the crystallites can grow without restriction due to the disappearance of OH-disorder-induced strain. Finally, for the In(OH)3 cuboids a three-step formation process is suggested: In the first step, one-dimensional OA under formation of nanorods occurs. In the second step, parallel bundles are formed from the nanorods. In the third step these bundles merge into cuboids by three-dimensional O

Precipitation of In(OH)3 and InOOH nanocrystals for the use in nanoelectronics: Phase transition behavior and oriented aggregation - Klaumünzer, Martin; Mackovic, Mirza; Ferstl, Pascal; Voigt, Michael; Spiecker, Erdmann; Meyer, Bernd; Peukert, Wolfgang (Nanotechnology 2013: Advanced Materials, CNTs, Particles, Films and Composites - 2013 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2013, 2013)
With respect to diverse applications in the wide field of nanoelectronics we characterize a specific phase transition behaviour and oriented aggregation (OA) during wet chemical synthesis of In(OH) nanocrystals as a wide band gap- and precursor material for InO. Contiguous to the cubic In(OH) phase, also orthorhombic InOOH is formed in a precipitation route with indium acetate as the In3+ source. Nano- and microcuboids are observed that consist exclusively of In(OH). The InOOH phase stays semi-crystalline even for long reaction times. On the basis of DFT calculations we find that for small crystallites the InOOH phase is more stable than the In(OH) phase, leading to a size-dependent transition from the InOOH phase to In(OH) above a critical crystallite size.
Keywords: Indium oxohydroxide; Nanocrystals; Oriented aggregation indium hydroxide; Precipitation

Production of dispersions with small particle size from commercial indium tin oxide powder for the deposition of highly conductive and transparent films - Mahajeri, Mahdi; Schneider, Andreas; Baum, Marcus; Rechtenwald, T.; Voigt, Michael; Schmidt, Michael; Peukert, Wolfgang (Thin Solid Films, 2012)
Indium tin oxide (ITO) nanoparticle films for applications in printable electronics were prepared by dip-coating. The dispersion conditions (bead size, stabilizer concentration) strongly affect the particle size of the ITO suspensions and consequently determine the surface morphology of the ITO films. Deposition from ethanolic ITO suspensions with an extremely small particle size of 17 nm to 21 nm led to the formation of extremely smooth and spike-free ITO films with a typical root mean square surface roughness of 4.5 nm +/- 0.2 nm and a high optical transparency above 95%. The effect of annealing with forming gas and CO2 laser treatment on the electrical properties of the ITO films was investigated. Annealing with forming gas and CO2 laser treatment led to a temporary increase in the electrical conductivity of the ITO films by up to a factor of 10 and 6, respectively. Specific conductivities of up to 196 S cm(-1) were obtained for our ITO nanoparticle films under optimized conditions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Indium tin oxide; Nanoparticles; Suspension; Conductivity; Laser treatment; Forming gas treatment

Scalable production of graphene sheets by mechanical delamination - Knieke, Catharina; Berger, Angela; Voigt, Michael; Klupp Taylor, Robin; Röhrl, Jonas; Peukert, Wolfgang (Carbon, 2010)
Mono- and multilayer graphene sheets have been successfully produced from commercial graphite powder in a wet grinding process under mild milling conditions. The shear forces in the milling chamber lead to a continuous delamination of ultrathin graphene flakes which are dispersed in a liquid medium. To avoid agglomeration of the exfoliated flakes the anionic surfactant sodium dodecyl sulfate was used. By adjusting the process parameters in a way to overcome the weak interlayer forces between the sheets without breaking them leads to the fabrication of thin flakes with high aspect ratios. The presented scalable process allows a high-yield and low-cost production of free-standing graphene sheets for various application
Keywords: monolayer; graphene; graphite; wet; grinding; interlayer; forces; flake; scaleable; sheet

Self-alignment of zinc oxide nanorods into a 3D-smectic phase - Schäfer, Stefan; Srikantharajah, Rubitha; Klaumünzer, Martin; Lobaz, Volodymyr; Voigt, Michael; Peukert, Wolfgang (Thin Solid Films, 2014)
We focus on thin films from ZnO nanorod dispersions in order to generate a high lateral order and a dense space filling structure applicable e. g. in printed optoelectronic devices. Highly stable dispersions with a solid content of up to 60 wt.% in ethanol were prepared using trioxadecanoic acid as stabilizer. With the dispersions we prepared thin films on substrates with a 3D-smectic phase in lateral dimension of cm2 and thicknesses from below 100 nm up to 1 μm. We show how the concentration of the initial solid content is influencing the formation of domains in our films and discuss the self-assembly process into ordered structures.

Size and shape engineering of ZnO nanoparticles - Klupp Taylor, Robin; Voigt, Michael; Segets, Doris; Peukert, Wolfgang; Marczak, Renata (2008 AIChE Annual Meeting, 2008)
The investigation of ZnO nanoparticles is of great interest due to the wide range of potential applications for this material. Despite this, a thorough understanding of the optical, electronic and structural properties of ZnO nanoparticles with respect to their synthesis is still lacking. We tackled this problem by synthesizing ZnO nanoparticles with nanocrystal, nanorod and self-assembled aggregate form using ambient and hydrothermal wet chemical processes. Dynamic light scattering, absorption and emission spectroscopies, thermogravimetric analysis, X-ray powder diffraction, Fourier infrared spectroscopy as well as transmission and scanning electron microscopies were employed to characterize and compare the nanoparticles composition, their shape, size and crystallinity. By varying different parameters of the synthesis processes like precursors and their concentrations, solvent used, surfactant, temperature, and reaction time we were able to control the size and shape of the particles. In particular we noted the tendency of ZnO nanocrystals to self-assemble into dense structures which preserve the anisotropic crystal structure. Using surface-mediating polymers such as PVP, this self-organisation could be modified so as to produce nanostructures with a tunable porosity, with great potential for application.
Keywords: ZnO; nanoparticle; nanostructure; growth; crystal; self-assembly

Surface functionalization of ZnO nanorods with C60 derivatives carrying phosphonic acid functionalities - Voigt, Michael; Klaumünzer, Martin; Ebel, Alexander; Werner, Fabian; Yang, Guang; Marczak, Renata; Spiecker, Erdmann; Guldi, Dirk Michael; Hirsch, Andreas; Peukert, Wolfgang (Journal of Physical Chemistry C, 2011)
ZnO with its wide band gap (3.37 eV) emerged as a promising semiconductor material for applications in the fields of printable and flexible electronics such as field effect transistors, etc. The fact that contacts at particle/particle interfaces exert a limiting impact on device performances motivates research on aligning the electronic levels at particle/particle interfaces. To this end, we focus in the present study on the surface functionalization of ZnO nanorods by a series of C derivatives. The latter share in common (i) a phosphonic acid as an anchor to ZnO, (ii) an alkyl chain as a flexible spacer, and (iii) a C as the headgroup. To shed light onto the electronic interactions between ZnO and C, we vary the alkyl chain length from n = 3 to n = 18. HRTEM and EELS prove the successful surface functionalization. Fundamental to this work are steady state absorption and photoluminescence measurements, which confirm the presence of appreciable electronic couplings between ZnO nanorods and C. Especially the photoluminescence measurements are important since they provide strong support for the dependence between spacer length and strength of electronic communication. In particular, a blue-shift of the ZnO free exciton emission band amounting to as much as 50 meV is observed with a decrease in spacer length. Furthermore, time-resolved absorption measurements corroborate ultrafast charge injection - facilitated by strong coupling - from the photoexcited ZnO nanorods to C. © 2011 American Chemical Society.
Keywords: Functionalization; Oxides; Reaction products; Organophosphorus compounds; Nanorods